Effectiveness of active labour market policies for job creation and earnings of the self-employed - Sandra M. Sánchez-Cañizares; L. Javier Cabeza-Ramírez; Ana M. Castillo-Canalejo; Francisco J. Rey-Carmona (Humanities & Social Sciences Communications)
Abstract Self-employed workers represent a significant share of the workforce in the main European countries. The recent COVID-19 crisis, followed by the conflict in Ukraine, has highlighted the unique challenges faced by this type of worker: income volatility, limited employment protection, and greater financial responsibility. In light of these challenges, it is essential to understand how active labour market policies influence their wage conditions (earnings) and ability to generate employment in order to ensure adequate employment protection and promote sustainable economic growth. This study analyses how the application of eight different policies affects self-employed people’s earnings and job creation, comparing participants and non-participants. Using an ad hoc survey, a random sample of 1265 self-employed people from the south of Spain was collected. The results of the propensity score matching method (PSM) and logistic regression models revealed that three types of ALMPs: free training programmes, low-interest loans, and the subsidy for hiring workers had a significant impact on job creation by the group of beneficiaries. Additionally, although training programmes and hiring subsidies showed positive effects on the average earnings of policy beneficiaries in the PSM analysis, these effects were not significantly verified when applying the logistic regression models. Despite the growing body of research that identifies the positive impacts of subsidies on self-employment outcomes, very little is known about the additional effects on earnings. We present the first estimation of the joint impact and provide policymakers with new evidence of the added value of training programmes and subsidies for hiring on earnings and job creation.